A modified natural graphite material and its preparation method and application

By adding modifiers in batches to the preparation of graphite materials, combined with cold isostatic pressure and spheroidized breakage treatment, the porosity and improvement of coating uniformity are solved, and graphite negative electrode materials are solved in the use of fast charging and high power. The problem of limited cycle performance achieves higher cycle performance.

CN116621168BActive Publication Date: 2025-02-07江苏凯金新能源科技有限公司
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310648181.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-02
Publication Date
2025-02-07
Estimated Expiration
2043-06-02

AI Technical Summary

Technical Problem

In the fast charging and high power use of existing graphite anode materials, the cycling performance is limited by the difficulty of lithium ions passing through the interface and the high porosity, resulting in increased interface reaction and irreversible cycling capacity loss.

Method used

By dividing the modifier into two parts, adding it in batches before isostatic pressure and after spheroidization and breaking treatment, combining cold isostatic pressure technology and spheroidization and breaking treatment, the porosity of the graphite material is reduced, and the porosity of the graphite material is reduced through Carbon coating achieves uniformity of coating.

Benefits of technology

It effectively reduces the porosity of graphite materials, improves the uniformity of coating, and improves the overall circulation performance of lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116621168B_ABST
    Figure CN116621168B_ABST
Patent Text Reader

Abstract

The present invention discloses a modified natural graphite material and a preparation method thereof. The preparation method comprises the following steps: (1) providing natural graphite and a modifier, wherein the mass ratio of natural graphite to modifier is 100:1-25, and the modifier is divided into a first part of the modifier and a second part of the modifier; (2) mixing the natural graphite and the first part of the modifier to obtain a mixture; (3) placing the mixture in an isostatic pressing device for densification treatment to obtain a first precursor; (4) crushing the first precursor, and then spheroidizing and dispersing the crushed precursor to obtain a second precursor; (5) mixing the second precursor with the second part of the modifier to obtain a third precursor; (6) carbonizing and sieving the third precursor to obtain modified natural graphite. The modified natural graphite material has a lower porosity and uniform coating. The present invention also provides the use of the modified natural graphite material in a negative electrode material of a lithium ion battery, so that the overall cycle performance of the lithium ion battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of graphite material preparation, and in particular to a modified natural graphite material and a preparation method and application thereof. Background Art

[0002] Graphite is currently the most popular negative electrode material for lithium-ion batteries. Products powered by mobile power cannot do without the support of graphite negative electrodes because graphite negative electrodes have high reversibility and stable cycle performance. With the rapid growth of the global electric vehicle market, improving the fast charging performance of graphite to reduce charging time and improve cycle performance has become a major research direction.

[0003] Graphite is widely used as a lithium-ion negative electrode material on a commercial scale because of its large reversible specific capacity and low working potential. Despite these advantages, the cycle performance of graphite negative electrodes has been put to the test as the market demand for fast charging and high power continues to increase. During the cycle of the graphite negative electrode, lithium ions are constantly embedded and removed through the SEI membrane. As the charge and discharge rate becomes faster and faster, more lithium ions will pass through the interface of graphite in a certain period of time, causing "traffic jams". In this process, the interface between graphite and the electrolyte may be damaged, causing problems such as capacity loss caused by SEI membrane rupture and re-reaction.

[0004] In order to solve the problem of lithium ions having difficulty passing through the interface, the market usually uses carbon coating to open certain channels for lithium ions on the surface of graphite. However, because the existing graphite negative electrode processing technology cannot perfectly control the morphology and specific surface area of ​​graphite powder, there are still many pores inside the graphite negative electrode powder after processing. During the carbon coating process, the auxiliary materials cannot evenly cover every surface. The higher porosity increases the probability of interface reaction during the cycle, resulting in irreversible cycle capacity loss. Therefore, it is necessary to improve this situation. Summary of the invention

[0005] In view of the above problems, the object of the present invention is to provide a modified natural graphite material and a preparation method thereof, which can effectively reduce the porosity of the graphite material and improve the uniformity of the coating, so as to improve the overall cycle performance of the lithium-ion battery.

[0006] To achieve the above object, the present invention provides a method for preparing a modified natural graphite material, comprising the steps of:

[0007] (1) providing natural graphite and a modifier, wherein the mass ratio of natural graphite to the modifier is 100:1-25, and the modifier is divided into two parts, a first part of the modifier and a second part of the modifier;

[0008] (2) mixing natural graphite with the first part of the modifier to obtain a mixture;

[0009] (3) placing the mixed material in an isostatic pressing device for densification to obtain a first precursor;

[0010] (4) crushing the first precursor, and then spheroidizing and breaking up the crushed precursor to obtain a second precursor;

[0011] (5) mixing the second precursor with the second portion of the modifier to obtain a third precursor;

[0012] (6) The third precursor is subjected to carbonization treatment and screening treatment to obtain modified natural graphite.

[0013] Compared with the prior art, the preparation method of the modified natural graphite material of the present invention divides the modifier into a first part of the modifier and a second part of the modifier, and adds the modifier in batches before isostatic pressing and after spheroidization and dispersion treatment to improve the density and reduce the porosity. In the process, cold isostatic pressing technology is also used to reduce its porosity, and spheroidization and dispersion treatment is used to ensure the regularity of the graphite negative electrode powder morphology. After completing the above steps, carbon coating is performed to achieve coating uniformity. The obtained modified natural graphite material has lower porosity and good coating uniformity. It is used for lithium ion battery negative electrode materials to improve the overall cycle performance of lithium ion batteries.

[0014] In some embodiments, the natural graphite is selected from at least one of flake graphite, spherical graphite, and microcrystalline graphite. By way of example, the natural graphite is spherical graphite or microcrystalline graphite, but is not limited thereto.

[0015] In some embodiments, in step (1), the modifier is selected from at least one of coal tar, petroleum asphalt, coal tar, natural asphalt, phenolic resin, epoxy resin, urea-formaldehyde resin, furfural phenol resin, furfuryl alcohol resin, polybutadiene resin, melamine formaldehyde resin, polyurethane, acrylic resin, polycarbonate, ethyl methyl carbonate, polymethyl methacrylate, polyaniline, polyimide, polyethylene glycol polyethyleneimine, poly-m-phenylenediamine, polypyrrole, polythiophene, polyacrylonitrile, polyvinyl chloride, polytetrafluoroethylene, polyvinylidene fluoride, polyphenylene sulfide, polyoxymethylene, polyethylene oxide, and polypropylene oxide. As an example, the modifier is petroleum asphalt or coal tar, but is not limited thereto.

[0016] It should be noted that the first part of the modifier and the second part of the modifier can be the same modifier or different modifiers. By way of example, the first part of the modifier is selected from at least one of coal tar, petroleum asphalt, coal tar, natural asphalt, phenolic resin, epoxy resin, urea-formaldehyde resin, furfural phenol resin, furfuryl alcohol resin, polybutadiene resin, melamine formaldehyde resin, polyurethane, acrylic resin, polycarbonate, ethyl methyl carbonate, polymethyl methacrylate, polyaniline, polyimide, polyethylene glycol polyethyleneimine, poly-m-phenylenediamine, polypyrrole, polythiophene, polyacrylonitrile, polyvinyl chloride, polytetrafluoroethylene, polyvinylidene fluoride, polyphenylene sulfide, polyoxymethylene, polyethylene oxide, and polypropylene oxide. As an example, the modifier is petroleum asphalt or coal tar, but not limited thereto; the second part of the modifier is selected from at least one of coal tar, petroleum asphalt, coal tar, natural asphalt, phenolic resin, epoxy resin, urea-formaldehyde resin, furfural phenol resin, furfuryl alcohol resin, polybutadiene resin, melamine formaldehyde resin, polyurethane, acrylic resin, polycarbonate, ethyl methyl carbonate, polymethyl methacrylate, polyaniline, polyimide, polyethylene glycol polyethyleneimine, poly-m-phenylenediamine, polypyrrole, polythiophene, polyacrylonitrile, polyvinyl chloride, polytetrafluoroethylene, polyvinylidene fluoride, polyphenylene sulfide, polyoxymethylene, polyethylene oxide, and polypropylene oxide. As an example, the modifier is petroleum asphalt or coal tar, but not limited thereto.

[0017] In some embodiments, the mass ratio of natural graphite to modifier is 100:1-25. Preferably, the mass ratio of natural graphite to modifier is 100:2-25, 100:5-25, 100:10-25, 100:15-25, 100:20-25, 100:5-20, 100:5-15, 100:10-20. Specifically, the mass ratio of natural graphite to the first part of the modifier is 100:1-25. Preferably, the mass ratio of natural graphite to the first part of the modifier is 100:1-20, 100:1-15, 100:1-10, 100:2-20, 100:2-15, 100:2-10, 100:3-10, 100:3-15, 100:3-20, 100:4-25, 100:4-20, 100:4-15, 100:4-10, etc., but this is not the case. limit; the mass ratio of natural graphite to the second part of the modifier is 100: 1 to 25, preferably, the mass ratio of natural graphite to the second part of the modifier is 100: 1 to 20, 100: 1 to 15, 100: 1 to 10, 100: 2 to 20, 100: 2 to 15, 100: 2 to 10, 100: 3 to 10, 100: 3 to 15, 100: 3 to 20, 100: 4 to 25, 100: 4 to 20, 100: 4 to 15, 100: 4 to 10, etc., but is not limited to this.

[0018] In some embodiments, the natural graphite and the first part of the modifier are mixed by a blending machine. Further, the blending machine adopts a stirring speed of 200 rpm / min to 1000 rpm / min, and the stirring time is 20 min to 1 h.

[0019] In some embodiments, the operating pressure of the isostatic pressing equipment is set to 60MPA-150MPA; the holding time is 10min-40min.

[0020] In some embodiments, the isostatic pressing equipment is a cold isostatic pressing equipment; and the pressure transmitting medium is water or oil.

[0021] In some embodiments, the crushing process in step (4) is performed by a crusher. By way of example, the crusher is an impact crusher, a jaw crusher, a cone crusher, a hammer crusher or an impact crusher.

[0022] In some embodiments, the particle size of the second precursor is D50=8-30 μm, that is, the spheroidization and dispersion process controls the particle size of the second precursor to be D50=8-30 μm. For example, the spheroidization and dispersion is performed using a spheroidization and dispersion device.

[0023] In some embodiments, in step (6), the temperature of the carbonization treatment is 750° C. to 1450° C., but not limited thereto.

[0024] In some embodiments, the carbonization treatment is carried out using equipment such as a box furnace, a rotary kiln, a roller kiln, a tunnel kiln, and a medium frequency furnace.

[0025] In some embodiments, the mesh size of the sieve used in the sieving process is 200-500 mesh, but is not limited thereto.

[0026] Correspondingly, the present invention also provides a modified natural graphite material, which is prepared by the above preparation method. The prepared modified natural graphite material has lower porosity and good coating uniformity.

[0027] Correspondingly, the present invention also provides an application of a modified natural graphite material in a negative electrode material of a lithium ion battery. The modified natural graphite material is used as a negative electrode material of a lithium ion battery to improve the overall cycle performance of the lithium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is the SEM image of the modified natural graphite material of Example 1.

[0029] Figure 2 This is the SEM image of the modified natural graphite material of Comparative Example 2.

[0030] Figure 3 This is the SEM image of the modified natural graphite material of Comparative Example 5. DETAILED DESCRIPTION

[0031] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present invention.

[0032] Example 1

[0033] The preparation method of modified natural graphite material comprises the steps of:

[0034] (1) 30 kg of spherical natural graphite and 700 g of petroleum asphalt were placed in a blending machine and mixed at a speed of 400 r / min for 50 min to obtain a mixture;

[0035] (2) placing the mixed material in a wet bag isostatic pressing device, pressurizing it to 100 MPA, and maintaining the pressure for 20 minutes; taking out the block graphite (the first precursor), crushing and rough breaking the block graphite with a hydraulic crusher, and directly using a spheroidizing and breaking device to spheroidize and break up the rough broken material to D50 = 17 μm, to obtain a second precursor;

[0036] (3) placing the second precursor and 1 kg of petroleum asphalt in a blender and mixing them at a speed of 400 r / min for 50 min to obtain a third precursor;

[0037] (4) The mixed third precursor is carbonized in a roller kiln at 1150° C. and sieved through 325 meshes to obtain a finished product, i.e., a modified natural graphite material.

[0038] Example 2

[0039] The preparation method of modified natural graphite material comprises the steps of:

[0040] (1) 30 kg of spherical natural graphite and 300 g of petroleum asphalt were placed in a blending machine and mixed at a speed of 400 r / min for 50 min to obtain a mixture;

[0041] (2) placing the mixed material in a wet bag isostatic pressing device, pressurizing it to 100 MPA, and maintaining the pressure for 20 minutes; taking out the block graphite (the first precursor), crushing and coarsely breaking the block graphite with a hydraulic crusher, and directly spheroidizing and breaking the coarsely broken material with a spheroidizing and breaking device to D50 = 12 μm, to obtain a second precursor;

[0042] (3) placing the second precursor and 1.4 kg of petroleum asphalt in a blender and mixing them at a speed of 400 r / min for 50 min to obtain a third precursor;

[0043] (4) The mixed third precursor is carbonized in a roller kiln at 1100° C. and sieved through 325 mesh to obtain a finished product, i.e., a modified natural graphite material.

[0044] Example 3

[0045] The preparation method of modified natural graphite material comprises the steps of:

[0046] (1) 30 kg of flake graphite and 950 g of petroleum asphalt were placed in a blending machine and mixed at a speed of 400 r / min for 50 min to obtain a mixture;

[0047] (2) placing the mixed material in a wet bag isostatic pressing device, pressurizing it to 100 MPA, and maintaining the pressure for 20 minutes; taking out the block graphite (the first precursor), crushing and rough breaking the block graphite with a hydraulic crusher, and directly using a spheroidizing and breaking device to spheroidize and break up the rough broken material to D50 = 20 μm, to obtain a second precursor;

[0048] (3) placing the second precursor and 750 g of petroleum asphalt in a blender and mixing them at a speed of 400 r / min for 50 min to obtain a third precursor;

[0049] (4) The mixed third precursor is carbonized in a roller kiln at 1250° C. and sieved through 325 mesh to obtain a finished product, i.e., a modified natural graphite material.

[0050] Example 4

[0051] The preparation method of modified natural graphite material comprises the steps of:

[0052] (1) placing 30 kg of spherical natural graphite and 1.25 kg of urea-formaldehyde resin in a blending machine, and mixing them at a rotation speed of 400 r / min for 50 min to obtain a mixture;

[0053] (2) placing the mixed material in a wet bag isostatic pressing device, pressurizing it to 100 MPA, and maintaining the pressure for 20 minutes; taking out the block graphite (the first precursor), crushing and rough breaking the block graphite with a hydraulic crusher, and directly using a spheroidizing and breaking device to spheroidize and break up the rough broken material to D50 = 17 μm, to obtain a second precursor;

[0054] (3) placing the second precursor and 450 g of urea-formaldehyde resin in a blender and mixing at a speed of 400 r / min for 50 min to obtain a third precursor;

[0055] (4) The mixed third precursor is carbonized in a roller kiln at 1150° C. and sieved through 325 meshes to obtain a finished product, i.e., a modified natural graphite material.

[0056] Comparative Example 1

[0057] The preparation method of modified natural graphite material comprises the steps of:

[0058] (1) placing 30 kg of spherical natural graphite and 1.7 kg of petroleum asphalt in a blending machine, and mixing them at a speed of 400 r / min for 50 min to obtain a mixture;

[0059] (2) placing the mixed material in a wet bag isostatic pressing device, pressurizing it to 100 MPA, and maintaining the pressure for 20 minutes; taking out the block graphite (the first precursor), crushing and rough breaking the block graphite with a hydraulic crusher, and directly using a spheroidizing and breaking device to spheroidize and break up the rough broken material to D50 = 17 μm, to obtain a second precursor;

[0060] (3) The second precursor is carbonized at 1150° C. using a roller kiln, and after carbonization, it is sieved through 325 mesh to obtain a finished product, i.e., a modified natural graphite material.

[0061] Comparative Example 2

[0062] The preparation method of modified natural graphite material comprises the steps of:

[0063] (1) placing 30 kg of spherical natural graphite in a wet bag isostatic pressing device, pressurizing to 100 MPA, and maintaining the pressure for 20 min; taking out the block graphite (the first precursor), crushing and coarsely breaking the block graphite with a hydraulic crusher, and directly spheroidizing and breaking the coarsely broken material with a spheroidizing and breaking device to D50 = 17 μm, to obtain a second precursor;

[0064] (2) placing the second precursor and 1.7 kg of petroleum asphalt in a blender and mixing them at a speed of 400 r / min for 50 min to obtain a third precursor;

[0065] (3) The mixed third precursor is carbonized in a roller kiln at 1150° C. and sieved through 325 meshes to obtain a finished product, i.e., a modified natural graphite material.

[0066] Comparative Example 3

[0067] The preparation method of modified natural graphite material comprises the steps of:

[0068] (1) 30 kg of spherical natural graphite with a D50 of 17 μm and 1.7 kg of petroleum asphalt were placed in a blending machine and mixed at a speed of 400 r / min for 50 min to obtain a mixture;

[0069] (2) The mixed material is carbonized in a roller kiln at 1150° C. and sieved through 325 meshes to obtain a finished product, i.e., a modified natural graphite material.

[0070] Comparative Example 4

[0071] The preparation method of modified natural graphite material comprises the steps of:

[0072] (1) 30 kg of spherical natural graphite and 700 g of petroleum asphalt were placed in a blending machine and mixed at a speed of 400 r / min for 50 min to obtain a mixture;

[0073] (2) placing the mixed material in a wet bag isostatic pressing device, pressurizing it to 100 MPA, and maintaining the pressure for 20 minutes; taking out the block graphite (the first precursor), crushing and coarsely breaking the block graphite with a hydraulic crusher, and grinding the coarsely broken material with a jet mill to D50 = 17 μm, thereby obtaining a second precursor;

[0074] (3) placing the second precursor and 1 kg of petroleum asphalt in a blender and mixing them at a speed of 400 r / min for 50 min to obtain a third precursor;

[0075] (4) The mixed third precursor is carbonized in a roller kiln at 1150° C. and sieved through 325 meshes to obtain a finished product, i.e., a modified natural graphite material.

[0076] Comparative Example 5

[0077] The preparation method of modified natural graphite material comprises the steps of:

[0078] (1) 30 kg of spherical natural graphite was placed in a wet bag isostatic pressing device, pressurized to 100 MPA, and maintained at the pressure for 20 min. The block graphite (first precursor) was taken out and crushed and roughly broken with a hydraulic crusher. The roughly broken material was directly spheroidized and broken with a spheroidizing and breaking device to D50 = 17 μm to obtain a second precursor;

[0079] (2) The second precursor is carbonized at 1150° C. using a roller kiln, and after carbonization, it is sieved through 325 mesh to obtain a finished product, i.e., a modified natural graphite material.

[0080] After the finished products obtained in Example 1, Comparative Example 2 and Comparative Example 5 are made into pole pieces, the pole pieces are cut, and the effects of the cut surface under an electron microscope are as follows: Figure 1 , Figure 2 , Figure 3 As shown. Figure 1-Figure 3 It can be seen that the internal pores of the particles in Example 1, Comparative Example 2 and Comparative Example 5 can be more intuitively seen under an electron microscope. Figure 1 Comparison Figure 2 and Figure 3 There are fewer internal cracks, indicating that the densification effect of Example 1 is better.

[0081] The modified natural graphite materials of Examples 1 to 4 and Comparative Examples 1 to 5 were subjected to performance tests, as follows:

[0082] The tap density was tested using Dandong Better BT-302 tap density tester;

[0083] The specific surface area was tested using a Micromeritics Surface Area Analyzer 3020;

[0084] The porosity was measured by mercury intrusion porosimetry using the American McPure 9500;

[0085] The electrical properties of the modified natural graphite materials of Examples 1 to 4 and Comparative Examples 1 to 5 were tested by a half-cell test method. The test method is as follows: the graphite material, a 6% N-methylpyrrolidone solution of polyvinylidene fluoride, and SP are mixed in a mass ratio of 92:4:4 and evenly coated on a copper foil. The electrode is then placed at 105°C for vacuum drying for 24 hours. The button cell is assembled in a glove box. The electrolyte is LiPF6 with a concentration of 1M, and the solvent is composed of dimethyl carbonate, ethylene carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:1. The counter electrode is a lithium sheet. The entire test is completed on an Arbin electrochemical detection system in the United States. The results are shown in Table 1.

[0086] Table 1 Test results

[0087]

[0088]

[0089] From the results in Table 1, it can be seen that by comparing Example 1 with Comparative Examples 1-2, the total amount of petroleum asphalt added remains unchanged. In the scheme of mixing 700g of petroleum asphalt before isostatic pressing and mixing 1kg of asphalt after isostatic pressing and spheroidization, the porosity is the lowest and the battery cycle performance is the best, indicating that adding petroleum asphalt in batches before and after densification treatment can effectively improve the densification energy and reduce the porosity.

[0090] From the test data of Example 1 and Comparative Example 3, it can be seen that the total amount of petroleum asphalt added remains unchanged, and Comparative Example 3 does not contain processes such as isostatic pressing and spheroidization and dispersion treatment. Its porosity is much higher than that of Example 1, and its cycle performance is also inferior.

[0091] It can be seen from the test data of Example 1 and Comparative Example 4 that the total amount of petroleum asphalt added remains unchanged, and Comparative Example 4 does not contain spheroidization and dispersion treatment. Air flow milling is used instead of spheroidization and dispersion treatment, so that the modified natural graphite powder obtained is more irregular in morphology than the spherical modified natural graphite obtained by spheroidization and dispersion equipment, which affects its vibration, specific surface, compaction and other powder indicators, and also affects the porosity, so that the cycle performance cannot be improved.

[0092] It can be seen from the test data of Example 1 and Comparative Example 5 that the finished product obtained by isostatic pressing the spherical natural graphite aggregate alone without adding a modifier has a high porosity and poor other properties.

[0093] In summary, the preparation method of the modified natural graphite material of the present invention divides the modifier into a first part of the modifier and a second part of the modifier, and adds them in batches before isostatic pressing and after spheroidization and dispersion treatment to improve the density and reduce the porosity. In this process, cold isostatic pressing technology is also used to reduce its porosity, and spheroidization and dispersion treatment is used to ensure the regularity of the graphite negative electrode powder morphology. After completing the above steps, carbon coating is performed to achieve coating uniformity. The obtained modified natural graphite material has lower porosity and good coating uniformity. It is used for lithium ion battery negative electrode materials to improve the overall cycle performance of lithium ion batteries.

[0094] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a modified natural graphite material, characterized in that: Includes steps: (1) providing natural graphite and a modifier, and dividing the modifier into two parts, a first part of the modifier and a second part of the modifier; (2) mixing natural graphite with the first part of the modifier to obtain a mixture; (3) placing the mixed material in an isostatic pressing device for densification to obtain a first precursor; (4) crushing the first precursor, and then spheroidizing and breaking up the crushed precursor to obtain a second precursor; (5) mixing the second precursor with the second portion of the modifier to obtain a third precursor; (6) subjecting the third precursor to carbonization and screening to obtain modified natural graphite; Among them, the mass ratio of natural graphite to modifier is 100:1-25; the mass ratio of natural graphite to the first part of modifier is 100:1-25, and the mass ratio of natural graphite to the second part of modifier is 100:1-25; the operating pressure of the isostatic pressing equipment is set to 60MPA-150MPA; the particle size of the second precursor D50=8-30μm.

2. The method for preparing the modified natural graphite material according to claim 1, characterized in that: In step (1), the natural graphite is selected from at least one of flake graphite, spherical graphite and microcrystalline graphite.

3. The method for preparing the modified natural graphite material according to claim 1, characterized in that: In step (1), the modifier is selected from at least one of coal tar, petroleum asphalt, coal tar, natural asphalt, phenolic resin, epoxy resin, urea-formaldehyde resin, furfural phenol resin, furfuryl alcohol resin, polybutadiene resin, melamine formaldehyde resin, polyurethane, acrylic resin, polycarbonate, ethyl methyl carbonate, polymethyl methacrylate, polyaniline, polyimide, polyethylene glycol polyethyleneimine, poly-m-phenylenediamine, polypyrrole, polythiophene, polyacrylonitrile, polyvinyl chloride, polytetrafluoroethylene, polyvinylidene fluoride, polyphenylene sulfide, polyoxymethylene, polyethylene oxide, and polypropylene oxide.

4. The method for preparing the modified natural graphite material according to claim 1, characterized in that: The holding time of the isostatic pressing equipment is 10 minutes to 40 minutes.

5. The method for preparing the modified natural graphite material according to claim 1, characterized in that: The temperature of the carbonization treatment is 750°C to 1450°C.

6. Modified natural graphite material, characterized in that, The method is prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the modified natural graphite material as claimed in claim 6 in negative electrode materials for lithium-ion batteries.

Citation Information

Patent Citations

  • Long-life modified natural graphite cathode material as well as preparation method and use thereof

    CN107814382A

  • Preparation method of long-circulation lithium ion battery graphite negative electrode material

    CN114883544A